Vaccinia Virus Intracellular Movement Is Associated with Microtubules and Independent of Actin Tails - Ward, Brian M. (American Society for Microbiology, 2001)
Two mechanisms have been proposed for the intracellular movement of enveloped vaccinia virus virions: rapid actin polymerization and microtubule association. The first mechanism is used by the intracellular pathogens Listeria and Shigella, and the second is used by cellular vesicles transiting from the Golgi network to the plasma membrane. To distinguish between these models, two recombinant vaccinia viruses that express the B5R membrane protein fused to enhanced green fluorescent protein (GFP) were constructed. One had Tyr(112) and Tyr(132) of the A36R membrane protein, which are required for phosphorylation and the nucleation of actin tails, conservatively changed to Phe residues; the other had the A36R open reading frame deleted. Although the Tyr mutant was impaired in Tyr phosphorylation and actin tail formation, digital video and time-lapse confocal microscopy demonstrated that virion movement from the juxtanuclear region to the periphery was saltatory with maximal speeds of >2 μm/s and was inhibited by the microtubule-depolymerizing drug nocodazole. Moreover, this actin tail-independent movement was indistinguishable from that of a control virus with an unmutated A36R gene and closely resembled the movement of vesicles on microtubules. However, in the absence of actin tails, the Tyr mutant did not induce the formation of motile, virus-tipped microvilli and had a reduced ability to spread from cell to cell. The deletion mutant was more severely impaired, suggesting that the A36R protein has additional roles. Optical sections of unpermeabilized, B5R antibody-stained cells that expressed GFP-actin and were infected with wild-type vaccinia virus revealed that all actin tails were associated with virions on the cell surface. We concluded that the intracellular movement of intracellular enveloped virions occurs on microtubules and that the motile actin tails enhance extracellular virus spread to neighboring cells.